The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.amepre.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ and Pharmacists’ Reported Implementation of Vaccination Practices for Adults

Abstract: This report highlights gaps in access to vaccines recommended for adults across the spectrum of provider specialties. Greater implementation of the Standards by all providers could improve adult vaccination rates in the U.S. by reducing missed opportunities to recommend vaccinations and either vaccinate or refer patients to vaccine providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The completion rate for the pharmacist survey was 89.1% (261 completed out of 293 that began the survey). Additional details on the survey methodology are available elsewhere [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The completion rate for the pharmacist survey was 89.1% (261 completed out of 293 that began the survey). Additional details on the survey methodology are available elsewhere [33].…”
Section: Methodsmentioning
confidence: 99%
“…Analyses were conducted from March to August 2017. To produce estimates more reflective of the national clinician and pharmacist populations, each sample was balance-weighted using a raking calibration procedure that aligned the responding sample to national benchmarks for respondents’ age, sex, race/ethnicity, occupation, work setting, and Census region as described elsewhere [33]. All survey estimates were computed using these final weights.…”
Section: Methodsmentioning
confidence: 99%
“…Providers in that setting provided a range of feedback including ‘if the [CDS alerts] are going to help me do my job, [it] should be welcomed’ to ‘they are often incorrect.’ 18 Despite vaccine recommendations in the provider setting, a 2018 study showed that providers assessed and recommended vaccines based on the ACIP immunization schedules, but often did not stock vaccines such as HPV, PCV13, and ZVL as readily as the community pharmacy. 19 Many studies have shown success with vaccine programs in the community pharmacy setting, but the patients were screened using paper forms instead of electronic CDS alerts. 2022…”
Section: Discussionmentioning
confidence: 99%
“…Other recent work assessing clinicians' implementation of the NVAC Adult Immunization Standards reported much higher assessment rates of adult patients' needs by pharmacists ( 84%) and internal and family medicine physicians ( 89%) for influenza and pneumococcal vaccinations. 32,33 However, those findings used a convenience sample comprising a more disparate and smaller set of pharmacists (n ¼ 261), with different survey questions. Such high levels of compliance should be interpreted with caution given pervasive low immunization rates and high unmet needs.…”
Section: Discussionmentioning
confidence: 99%